Técnicas de correlação no delineamento de feições rodoviárias em imagens de baixa e média resolução - Mendes, Tatiana Sussel Gončalves [UNESP]; dal Poz, Aluir Porfírio [UNESP]; Fazan, Antonio Juliano [UNESP] (My University, 2010)
This paper presents a method for the sequential road feature delineation from digital images. It is based on a feedback loop between extrapolation and refinement steps of a given road centerline point, using in both steps correlation techniques. Firstly, a previously extracted road centerline point is linearly extrapolated, resulting in an approximate position. Secondly, this approximate position is corrected by comparing gray level profiles extracted perpendicularly to the extrapolation direction. This strategy is then repeated to allow the entire road centerline to be extracted or a stop point to be found. In order to initialize the extraction process, the operator needs to supply a starting point plus direction and width. Experimental results obtained from the application of the method to real image data are presented and discussed in this paper.
Correlation techniques for road delineation from low and medium resolution images
Keywords: Aerial images; Correlation techniques; Road delineation